(untitled) (World Bulletin of Management and Law, 2025)
Within the framework of the relations of the rights and obligations of the customer – patient and medical organization, as well as the provision of medical services, the issue of interested persons, the organization of the health insurance organization and legal liability are scientifically analyzed in medical service contracts